Pediatric sleep outcomes after endoscopy-directed simultaneous lingual tonsillectomy and epiglottopexy - Matthew Maksimoski; Sarah E. Maurrasse; Stephen R. Hoff; Jennifer Lavin; Taher Valika; Dana M. Thompson; Jonathan B. Ida (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The purpose of this study was to evaluate the efficacy of sleep endoscopy-directed simultaneous lingual tonsillectomy and epiglottopexy in patients with sleep disordered breathing (SDB), including polysomnography (PSG) and swallowing outcomes. Methods A retrospective review was performed of all patients undergoing simultaneous lingual tonsillectomy and epiglottopexy over the study period. PSG objective measures were recorded pre- and postoperatively, along with demographic data, comorbidities, and descriptive data of swallowing dysfunction in the postoperative setting. Results A total of 24 patients met inclusion criteria for consideration, with 13 having valid pre- and postoperative PSG data. Successful surgery was achieved in 84.6% of patients, with no difference based on presence of medical comorbidities including Trisomy 21. Median reduction in obstructive apnea–hypopnea index (oAHI) with the procedure was 69.9%. Four patients (16.7%) had postoperative concern for dysphagia, but all objective swallowing evaluations were normal and no dietary modifications were necessary. Conclusion Combination lingual tonsillectomy and epiglottopexy in indicated patients has a high rate of success in this single-institutional study without new dysphagia in this population. These procedures are amenable to a combination surgery in appropriately selected patients determined by sleep state endoscopy in the setting of SDB evaluated with drug-induced sleep endoscopy. Graphical abstract